The referee's challenge: a threshold process model for decision making in sport games. Issue 1 (1st January 2021) - Raab, Markus; Avugos, Simcha; Bar-Eli, Michael; MacMahon, Clare
ABSTRACT: Judgment and decision making in sporting officials is a challenging task that involves the use of context. Although process models of decision making describe decision contexts, none of the existing models explains when sports officials use rule-driven decision making, or game management. The basic idea of our work is that referees use a subjective threshold to apply game management, which may explain this decision behavior. We propose a new dynamic threshold model that is based on concepts derived from Decision Field Theory. The model includes two thresholds of game management (high/low) and two contact situations (foul/no foul) as approaching one of these thresholds. Using the example of soccer refereeing, we argue that if the game hits a subjective threshold of aggressive play, then the referee shifts from applying the rules to managing the game. This new approach changes the scientific discussion from one focused on what referees should decide in one situation or the other, to a dynamic model that explains the basic psychological mechanism underlying the referee's change in behavior during the game, both at the intra-individual as well as inter-individual level.